Increased production of pyocyanin in recombinant Pseudomonas aeruginosa PS39-phzMS strain harboring the pUCP24-phzMS plasmid - Quang Vinh, Nguyen; Hoang Uyen, Nguyen; Chi Thuan, Nguyen; Thi Thanh Loi, Nguyen (Vietnam Journal of Biotechnology, 2022)
PhzM and PhzS are two “core” enzymes that are necessary for conversion of phenazine-1-carboxylic acid (PCA) into pyocyanin (PYO) phenazine in Gram (-) bacterium Pseudomonas aeruginosa. Apparently, the raise in copy number of their genes could increase the amount of pyocyanin phenazine in the microbe. In previous research, two genes phzM and phzS originated from Pseudomonas aeruginosa PS39 strain had been inserted into a Pseudomonas – Escherichia coli shutlle vector pUCP24 to generate a plasmid pUCP24-phzMS. The obtained plasmid had been transformed into P. aeruginosa PS39 strain to create the recombinant P. aeruginosa PS39-phzMS strain. In this study, pUCP24-phzMS was sequenced to verify the polycistronic expression cassette containing both phzM and phzS genes. The results demonstrated that the recombinant plasmid comprised the ori of Pseudomonas and E. coli, gentamicin resistance-cassette, and polycistronic expression cassette for expression of PhzM and PhzS. In which, both genes will be transcripted together in one mRNA strand by the regulation of Lac promoter and operator. The translation from the mRNA to the corresponding proteins will be started by binding ribosome into RBS located upstream of each gene. The nucleotide sequence of these genes were completely homologous (100%) to the submitted sequences MF673740 (phzM) and MF770713 (phzS) on the NCBI GenBank database. Result on assessing the synthesis of pyocyanin in the recombinant strain with the presence of pUCP24-phzMS plasmid showed that pyocyanin concentration in the recombinant strain increased significantly over 2 times (31.22 mg/mL) more than that in the wild strain (13.47 mg/mL). The absorbance at 360 nm of PCA from the P. aeruginosa PS39-phzMS (OD367 = 0.03) strain decreased significantly compared to the one from wild type strain (OD367 = 0.39). Therefore, the plasmid with phzM and phzS genes was proved to improve the pyocyanin biosynthesis through a better conversion of PCA phenazine into PYO via PhzM and PhzS enzymes.